Sustainable E-Waste Management through Industry 5.0 - Chaitankar, Archana (International Journal of Advances in Business and Management Research (IJABMR), 2025)
Rapid technological advancements have led to a substantial demand for electronics products, resulting in the significant expansion of the electronics and hardware industry. Shifts in the characteristics of electronic devices and the presence of enhanced products compel consumers to quickly discard their electronic products. This has led to the generation of e-waste in huge quantities. E-waste poses a health risk because it contains harmful materials such as lead (Pb), hexavalent chromium (Cr⁶⁺), mercury (Hg), cadmium (Cd), and flame retardants like polybrominated biphenyls and polybrominated diphenyl ethers, among others. The management of electronic waste (E-waste) is a major issue in numerous developing nations. Disposing of e-waste with regular municipal trash poses a considerable threat to the environment in developing countries, where there is a deficiency of proper recycling methods and unregulated individuals resort to crude techniques to extract valuable metals for quick profits. To lessen detrimental environmental and public health effects, e-waste must be treated appropriately. The world is now moving towards Industry 5.0 and this industrial revolution focuses on human process integration with social and sustainability aspects. It highlights the human-machine interfaces in the value-creation aspect of business activities to eliminate social constraints. This article explores sustainable management of electronic waste in the context of Industry 5.0.